ANXIETY AND DEFENESE MECHANISMS PORTRAYED IN “CAT ON A HOT TIN ROOF” - Mujad Didien Afandi; Tatik Muflihah; Novi Rahmania Aquariza (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2022)
Born and raised in a poor family, a childless woman named Margaret who is a wife of an alcoholic, has an ambition for wealth which eventually causes her to live with anxiety. To suppress the anxiety, she uses defense mechanisms. Therefore, this study was conducted to analyze the anxiety and defense mechanisms portrayed through Margaret in the drama, entitled “Cat on a Hot Tin Roof”. This qualitative study analyzed the anxiety and defense mechanisms portrayed in one of the canonical drama of Tennessee Williams using psychological lens. The data describing Margaret's anxiety and defense mechanisms collected from this drama were revealed and interpreted descriptively in order to provide detailed explanation and deep understanding. This study identified that the anxiety experienced by Margaret was resulted from her ambition to inherit the wealth of her father-in-law. Poverty in her past life has led her to become ambitious to pursue her dreams of wealth. Besides, she got anxious about her inability to give a child to her husband. In consequence, her childlessness caused her to have anxiety. To cope with the anxiety, she used three types of defense mechanisms: (1) reaction formation, (2) displacement, and (3) denial.  The female major character experiences anxiety about wealth and childlessness. To protect herself from the anxiety, she uses reaction formation, displacement, and denial as defense mechanisms.